2016
DOI: 10.1111/fwb.12781
|View full text |Cite
|
Sign up to set email alerts
|

Dammed rivers: impoundments facilitate fish invasions

Abstract: 1. River damming and other anthropogenic disturbances of natural habitats are among the main drivers of species loss through a range of direct and indirect effects. While the effects of river damming on aquatic species are relatively well studied, particularly with regard to their impacts on diadromous species and stenotopic riverine specialists, there is a paucity of studies quantifying the effects of dam construction on whole communities. 2. We conducted a global meta-analysis focussed on fish communities, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 50 publications
4
58
1
Order By: Relevance
“…The impacts of dams on fish biodiversity followed a clear gradient across latitudes, from a general lack of diversity changes in boreal regions to substantial ones in the tropics. A previous meta‐analysis by Liew et al () suggested that dams have similar effect across regions, but their analyses did not consider the boreal region. In addition, our analyses are based on a substantially larger pool of information, representing a 60% increase in number of references considered by Liew et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of dams on fish biodiversity followed a clear gradient across latitudes, from a general lack of diversity changes in boreal regions to substantial ones in the tropics. A previous meta‐analysis by Liew et al () suggested that dams have similar effect across regions, but their analyses did not consider the boreal region. In addition, our analyses are based on a substantially larger pool of information, representing a 60% increase in number of references considered by Liew et al ().…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta‐analysis by Liew et al () suggested that dams have similar effect across regions, but their analyses did not consider the boreal region. In addition, our analyses are based on a substantially larger pool of information, representing a 60% increase in number of references considered by Liew et al (). As such, the gradient of effects we report on here clearly underscores the need for an understanding of regional fish assemblages, and the context of stressors when evaluating the impacts of damming rivers on fish biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we demonstrated the probable mechanisms of food web assembly. Our study sites were well‐suited in addressing this critical question in ecology because reservoirs represent a novel habitat type often associated with fluxes in community assemblages driven by species turnovers (Liew et al b ). The sites also shared a common pool of potential colonizers of roughly equal propagule pressure/dispersal probabilities because of Singapore's unique geography (i.e., small island with high levels of accessibility).…”
Section: Discussionmentioning
confidence: 99%
“…The buffering of extreme flows due to flow management favours fish and mussel species that have preference for stable ecosystem conditions (McManamay & Frimpong, ). The presence of reservoirs and flow regulation may also be responsible for changes on fish communities by promoting invasive species (Clavero, Hermoso, Aparicio, & Godinho, ; Liew, Tan, & Yeo, ), which can displace natives (Hermoso, Clavero, Blanco‐Garrido, & Prenda, ; Marchetti, Light, Moyle, & Viers, ; Marchetti & Moyle, ), a situation that will likely affect the fish–mussel relationship (Brainwood et al., ; Watters, ) with possible implications for mussel conservation (see below).…”
Section: Changes In the Fish Fauna And Their Interaction With Freshwamentioning
confidence: 99%